Предмет: Математика,
автор: ivanivanov2002
решите уравнение))
(3-х)(х+2)=0
Ответы
Автор ответа:
1
3x+6-x2-2x=O
-x2+x+6=O
x2-x-6=O
D= b2-4ac= 1-(4*(-6) ) = 1 + 24 = 25
x1= (1+5)/2=3
x2=(1-5)/2=-2
-x2+x+6=O
x2-x-6=O
D= b2-4ac= 1-(4*(-6) ) = 1 + 24 = 25
x1= (1+5)/2=3
x2=(1-5)/2=-2
Автор ответа:
2
3-х₁=0
х₁=3
х₂+2=0
х₂=-2
х₁=3
х₂+2=0
х₂=-2
Похожие вопросы
Предмет: Русский язык,
автор: fanatua
Предмет: Другие предметы,
автор: NONICKNAMElolKeK
Предмет: Окружающий мир,
автор: mama12011987
Предмет: Математика,
автор: anigreshnik
Предмет: Математика,
автор: karinarodimina